How is the User Experience on the ITSCREDIT website? - Canjangue, Maria Helena Barata (2022)
Nowadays it is fundamental to communicate clearly what a company has to offer to its potential customers especially online via a website. Multiple B2B websites fail to do so by not providing the customers the answers to fundamental questions and concerns. User Experience also known as UX carries a considerably important role in increasing user satisfaction by creating and providing services or products that guarantee relevant and meaningful experiences. Hence to create a website that offers all of the best experiences the design should be informative, easily navigated and intuitive. This thesis aims to describe the current user experience on the ITSCREDIT website and showcase and support any changes in the offerings by improving their overall website user experience, website navigation and information architecture. This thesis used qualitative research method involving 6 interviewees to understand user’s behaviors and patterns and according to the answers collected many found that the basics of the website were well structured and designed but was lacking in information relevancy and carried complex navigation throughout their experience which meant spending longer amounts of time and effort. Another qualitative method was also conducted to add further knowledge to the already conducted interviews. Through this quantitative method, it was discovered that the website carried too much information which made participants overwhelmed and distracted them from completing simple tasks. To be able to provide better visibility of progress, the thesis based its findings and evaluations on the UX design process created for ITSCREDIT, where Discovery, User Research, Design and Validation aid in achieving the specific goals of the thesis. During the discovery phase, the reader can understand about the company’s industry and present-day website. The research was implemented to gather insight, analyze the current website performance and give recommendations for improvement. The evaluation of usability and content of significant pages of the website were accomplished by analysis based on Nielsen’s Usability Principles. Through the discovery and user research phase analysis of primary and secondary data it was detected that there was a high margin of expectation between customer and what the website delivered. And based on the results obtained in both phases recommendations were provided for improvement of the user experience of the website.